Alternative anti-coagulant agents for natural rubber latex - Abu Hassan, Aziana; Jaswan Singh, Manroshan Singh; Saad, Wan Zuhainis; Mohamad, Rosfarizan (2015)
Ammonia is the most favourable anti-coagulant agent for natural rubber (NR) latex preservation. Evolution of NR latex preservation via the chemical based format had always been the preferable alternative. However, with increased awareness regards to the impact of chemicals to the environment and the community, research is now directed towards finding an alternative to chemicals using biologically derived substances. An attractive alternative is by the microbial derived substance as a biological based format. Fungal extracts from Aspergillus sp. MRB25 performing equally well as field NR latex stabilized with ammonia and streptomycin sulphate. Hence, using the biological pathway to produce extracts from microorganisms as anti-coagulant agent for NR latex preservation revealed a promising outcome.